2012
DOI: 10.14712/23361964.2015.53
|View full text |Cite
|
Sign up to set email alerts
|

Protocorms of an epiphytic orchid (Epidendrum amphistomum A. Richard) recovered in situ, and subsequent identification of associated mycorrhizal fungi using molecular markers

Abstract: ProtocormS of an EPiPhytic orchid (EpidEndrum amphistomum a. richard) rEcovErEd in situ, and SubSEquEnt idEntification of aSSociatEd mycorrhizal fungi uSing molEcular markErS L aw r ence w. Z et t L er 1, * , L au r a L . cor ey 1 , L a r ry w. r ich a r dson 2 , a pr i L y. ros s 1, 3 , and L i L L i a n MoL L e r-Jacob s 1, 4 1 department of biology, illinois college, 1101 west college avenue, Jacksonville, iL 62650 usa 2 Florida panther national wildlife refuge, u.s. Fish and wildlife service, 3860 tollgat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
0
16
1
Order By: Relevance
“…The distribution of mycorrhizal fungi associated with epiphytic orchids is less well studied, perhaps because early seed packet techniques using slide mounts were less successful on branches than in the ground (Zettler et al ., ). Otero et al .…”
Section: Local‐scale Dynamicsmentioning
confidence: 97%
See 1 more Smart Citation
“…The distribution of mycorrhizal fungi associated with epiphytic orchids is less well studied, perhaps because early seed packet techniques using slide mounts were less successful on branches than in the ground (Zettler et al ., ). Otero et al .…”
Section: Local‐scale Dynamicsmentioning
confidence: 97%
“…Additional experimental manipulation of environments and mycorrhizal fungi will provide further insight into the mechanisms behind observed patterns of orchid and fungus distribution. The distribution of mycorrhizal fungi associated with epiphytic orchids is less well studied, perhaps because early seed packet techniques using slide mounts were less successful on branches than in the ground (Zettler et al, 2011). Otero et al (2002) suggested that epiphytic orchids may also be affected by the distribution and abundance of their mycorrhizal fungi, but research is only beginning on mycorrhizal fungus distribution in epiphytes (Kartzinel et al, 2013).…”
Section: Local-scale Dynamicsmentioning
confidence: 99%
“…(), Zettler et al . (, , , ), and Zettler & P iskin (). The illustration of orchid phylogeny is based on data from C hase et al .…”
Section: Evolution Through Host Changesmentioning
confidence: 99%
“…The seed baiting technique initially developed by Rasmussen and Whigham (1993) has helped considerably with the former, resulting in more than a hundred studies carried out in situ during the past 20 years, mostly involving terrestrial orchids (Rasmussen, 2002). For epiphytic orchids, a modified seed baiting technique has since been developed that emphasizes affixing seed packets to arboreal substrates (Zettler et al 2011;Zi et al 2014) which may have potentials for use in a wide range of taxa. Nevertheless, seeds in packets that are attached to aerial substrates are highly vulnerable to desiccation, even in packets placed in direct contact with (moist) moss in continuous shade.…”
mentioning
confidence: 99%
“…Nevertheless, seeds in packets that are attached to aerial substrates are highly vulnerable to desiccation, even in packets placed in direct contact with (moist) moss in continuous shade. Zettler et al (2011) reported that only one of 60 seed packets affixed to trees harbored protocorms of Epidendrum amphistomum in south Florida, for example, and they proposed that moisture-rich substrates were needed for fungal growth and proliferation to trigger epiphytic orchid seed germination. If true, it is conceivable that placing a water absorbing/retaining material within the seed packet itself may raise moisture to levels conducive to germination.…”
mentioning
confidence: 99%